Analisis Penerapan Transit Oriented Development (TOD) pada Light Rail Transit (LRT) di Kota Palembang, Sumatera Selatan - Muhammad Fajri Romdhoni; Tutur Lussetyowati; Desi Amalia; Sindi Mawarni; Hafizah Al Fhatanny; Sarifah Hairunnisa Fitri Al-Qudusih (Archvisual: Jurnal Arsitektur dan Perencanaan, 2023)
Light Rail Transit (LRT) is one form of mass transportation using light rail train that reflect towards sustainable development has been planned by the South Sumatera local government. The benefits of LRT is to overcome the problem of traffic congestion using diversion for private vehicles users, to be mass transportation users, especially in the City of Palembang. LRT has become an alternative mode of transportation that is accessible, punctual, and it has a separate pathway from the existing transporting roads. The Light Rail Transit (LRT) in Palembang was built in 2018 as a form of development from the South Sumatra Provincial government for the 2018 Asian Games, the Southeast Asia regional sporting competition. Presenting LRT as a solution to traffic problems through sustainable development by the regional government to realize the concept of transit-oriented development (TOD)). The purpose of this study is to interogate the application of TOD in Palembang City, especially in the existence of LRT based on methods and approaches using TOD Indicators, such as: diversity, destination accessibility, distance & design, and demand management to encourage and realize the concept of transportation and development of Palembang City which is sustainable.